DIPG-73. CLEE011XUS17T (NCT 02607124): A PHASE I/II STUDY OF RIBOCICLIB (LEE011) FOLLOWING RADIATION THERAPY (RT) IN CHILDREN AND YOUNG ADULTS WITH NEWLY DIAGNOSED NON-BIOPSIED DIFFUSE PONTINE GLIOMAS (DIPG) AND RB+ BIOPSIED DIPG AND HIGH GRADE GLIOMAS (HGG). Issue 2 (22nd June 2018) - DeWire, Mariko; Fuller, Christine; Hummel, Trent; Chow, Lionel; Salloum, Ralph; Pater, Luke; Drissi, Rachid; Lu, Qing; Stevenson, Charles; Lane, Adam; Breneman, John; Witte, David; et al.
Abstract: INTRODUCTION: Dysregulation of the cyclin dependent kinase-retinoblastoma (CDK-RB) pathway is observed in DIPG and HGG. Ribociclib (LEE011) is an oral inhibitor of CDK4/CyclinD1 and CDK6/CyclinD3 complexes that induces RB hypophosphorylation and cell-cycle arrest. METHODS: Eligible patients with newly-diagnosed DIPG or HGG received ribociclib at the recommended phase 2 dose (RP2D) 350 mg/m 2 /day once daily for 3 weeks/one week off every 28 days following radiation therapy. Feasibility endpoints included tolerability of ribociclib at least 6 courses, > 2 weeks delay in the start of any course or discontinuation of the protocol therapy after one dose modification. Early efficacy was measured by overall survival (OS). PROMIS assessments were completed prospectively in eligible patients. RESULTS: Among 11 patients enrolled, ten were evaluable patients (median age: 7.5 years, range: 3.8–20.1; 9 DIPG, 1 HGG), three patients required dose reduction for grade 4 neutropenia; one patient came off therapy for hematological toxicity following course 4. The median number of courses was 7 (range: 3–14). The most common Grade 3/4 toxicity was myelosuppression. After two cycles of therapy, MRI evaluations in five patients revealed increased necrotic volume, associated with new neurological symptoms in three patients. The median OS for DIPG was 15.5 months (range: 10–17+). Three remain alive. OS for HGG patient was six months. CONCLUSION: Ribociclib administered post radiation therapy is feasible in this patient population. Increase in necrosis may represent treatment effect. Volumetric measurements warrant further investigations in evaluating tumor when necrosis is present. Correlative studies will be presented at the meeting.